ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP SIKAP DAN PERILAKU MEMBELI BUKU BAJAKAN PADA MAHASISWA IPB - Retnaningsih Retnaningsih; Puspa Widya Utami; Istiqlaliyah Muflikhati (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The aim of this research was to analyze factors which influence IPB students attitudes and buying behaviour of piracy book. Research method used cross sectional study design. The primary data from samples was collected along Mei 2009. Data was taken from 100 girls and 100 boys as samples of this research. The samples chosen by proportional sampling in each faculty of IPB. The data consist of primary data and secondary data. Data was analyzed by descriptive and inferential statistic (Mann-Whitney, t-test, multivariate regression, and logistic regression). The result showed that almost samples readed books and mostly they bought a book on the last three months. Almost of them had knowledge about piracy book with average level. Meanwhile, the attitude of the samples to piracy book were neutral. Factors that influenced attitude to piracy book were ages, money allocation, information resources, and level of knowledge. Then, attitude to piracy book was the factor that influenced buying behavior of piracy book.